Social Isolation and Its Impact on the Geriatric Community. Issue 3 (July 2021) - Ferreira, Germaine; Walters, Amy; Anderson, Hazel
Abstract : Causes of social isolation and loneliness in older adults are multifactorial and can have significant effects on their health and quality of life. Older adults who have good social support exhibit lower levels of depression, higher levels of life satisfaction, lower stress levels, and lower health care costs. By assessing and addressing social isolation and loneliness in community-dwelling older adults, rehabilitation therapists can have a positive impact on their physical and mental health.